Experimental investigation and optimization of flank wear during machining process using response surface methodology. (2022) - Surakasi, Raviteja; T.Rajendiran,; Narayan, Puneet; Santhosh Kumar, S.; Janardhana, Kedri; Pradhan, Raghuram
Abstract: Optimization is the process of obtaining best results from a given set of values. The applications of optimization process are found in several areas which include engineering, construction, managerial decision etc. CNC machining of Inconel 718 was selected for study. The flank wear is investigated as the response with the aid of vortex tube and without the aid of vortex tube. Regression equation is also obtained and the contour and surface plots are plotted. The flank wear is compared and it is found that the improvement in minimization of flank wear is upto 7% and it is satisfactory. The main aim of this work is to attain sustainability in conventional machining and the sustainability is attained in end milling using vortex tube. Validation of result was done using optimization technique.